Estudo comparativo entre PMBOK e o PDP para a gestão do processo de desenvolvimento de produto:um estudo de caso na indústria de ônibus - Zilio, Diego Muner (2016)
The bus industry is facing a decisive moment in front of the economic crisis that affecting the country, a fact that does not allow errors in the branch companies, companies seek to increase assertiveness in developing new products, ensuring it is market position. Therefore, the expansion of knowledge in project management it is opportune, and the companies will recognize the need to plan and manage their projects through this knowledge, especially applying them to new developments. From this perspective, the present study aims to develop a procedure for product development management, applying good management practices of the PMBOK. Therefore, it presents a theoretical framework through which are performed contextualization and lifting the guide tools, identifying the intersection of the same in the product development chain. For this, it analyzed in detail the development process practiced in the industry concerned, mapping and identifying its phases and gates approval. Thus, a contextualization and lifting the guide tools is accomplished by identifying the intersection of these in the product development chain, thus, based on this information is designed to PDP management procedure, which optimizes the application of project management tools, according to the object company needs to study this work. The results obtained by applying the procedure consist of the validation of the same front the reality found as the company's difficulties in PDP were also obtained benefits such as greater assertiveness in achieving the project objectives, realization of complete documentation for the product development and their approvals. As well, satisfactory results were obtained for the application of PMBOK tools where which complemented the development of the GPDP procedure, providing gains in certain phases of the project.